Accusative alignment in the Old Tibetan switch reference system - Hill, Nathan (My University, 2022)
The use of ནས་ -nas to mark cross-clausal co-reference in Version I of the Old Tibetan Rāmāyaṇa reveals accusative alignment in Tibetan syntax, which in turn vindicates the notion of ‘subject’ applied to Tibetan.
ACCEPTED
Keywords: Tibetan; Ergativity; Old Tibetan; Rāmāyaṇa